2021
DOI: 10.21203/rs.3.rs-907854/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Women Entrepreneurs and The usage of social Media for Business Sustainability In the time of Covid-19

Abstract: This study explores the efforts of Indonesian women entrepreneurs to sustain their businesses during the COVID-19 crisis of 2020–2021. Focusing on female-owned businesses in Yogyakarta, this research places particular emphasis on how social media contributes to their survival. Using a quantitative approach to analyze data collected from 130 respondents, the researchers found that the pandemic has severely affected women entrepreneurs—especially those operating SMEs. Most significantly, women have experienced r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Studies have found product diversification as a strategy employed by women business owners during the pandemic (Indrawati et al. , 2021; Rahayu et al. , 2021; Lawrence and Lawrence, 2021).…”
Section: Lack Of Financial Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found product diversification as a strategy employed by women business owners during the pandemic (Indrawati et al. , 2021; Rahayu et al. , 2021; Lawrence and Lawrence, 2021).…”
Section: Lack Of Financial Supportmentioning
confidence: 99%
“…(2021) reveal that women entrepreneurs are likelier to benefit from social media and promotions than any other method regarding minimizing sales loss. The COVID-19 pandemic continues to propel women entrepreneurs into the digital space as they aim to reach a broader range of customers (Rahayu et al. , 2021).…”
Section: Lack Of Financial Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Women entrepreneurs, not only in developed countries but also those that are developing, face various challenges, including access to the international market, but developed technology and various social networks are their biggest support, through which they can develop their businesses and access international markets [17][18][19]. Also, Rah et al [8] claimed that women entrepreneurs in developing countries, due to different traditional and cultural customs, as well as their lack of support, started their businesses, and accessing the operating market was easier through social media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Almost all businesses today also conduct their activities online, especially after the period of the COVID-19 pandemic. Businesses led by women, which are mostly small businesses, have their greatest development through social media, as they face various problems, where the most prominent ones are adaptation to technological changes, where the latter is developing with big steps in recent years, cooperation with qualified people, as well as balancing family and work [7,8]. This way of doing business is very welcome, especially for female entrepreneurs, since they can develop their businesses even without investments in facilities.…”
Section: Introductionmentioning
confidence: 99%